2015
DOI: 10.1103/physrevb.92.195403
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Raman scattering and weak localization in graphene deposited on GaN nanowires

Abstract: The influence of GaN nanowires on the optical and electrical properties of graphene deposited on them was studied using Raman spectroscopy and a microwave-induced electron transport method. It was found that the interaction with the nanowires induces spectral changes and leads to a significant enhancement of the Raman scattering intensity. Surprisingly, the smallest enhancement (about 30-fold) was observed for the defect induced D' process and the highest intensity increase (over 50-fold) was found for the 2D … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…[3] Our previous studies completed on graphene deposited on gallium nitride nanowires (GaN NWs) with similar height have shown that the Raman spectra of graphene are enhanced by more than an order of magnitude, when compared to graphene deposited on a GaN epilayer. [4] This enhancement has been interpreted to be caused by Surface Enhanced Raman Scattering (SERS). There are typically two mechanisms of SERS, an electromagnetic mechanism (EM) and a chemical mechanism (CM), and it is still under debate which of them is dominant in graphene.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Our previous studies completed on graphene deposited on gallium nitride nanowires (GaN NWs) with similar height have shown that the Raman spectra of graphene are enhanced by more than an order of magnitude, when compared to graphene deposited on a GaN epilayer. [4] This enhancement has been interpreted to be caused by Surface Enhanced Raman Scattering (SERS). There are typically two mechanisms of SERS, an electromagnetic mechanism (EM) and a chemical mechanism (CM), and it is still under debate which of them is dominant in graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of graphene deposited on vertically aligned gallium nitride nanowires (GaN NWs) are interesting not only because of possible applications in photovoltaics but also because of the presence of surface-enhanced Raman scattering in graphene. [1], [2], [3] Intensity of Raman bands has been found to be more than one order of magnitude higher than in graphene deposited on GaN epilayer. Our previous results have excluded light interference in NWs layer to be responsible for this enhancement.…”
Section: Introductionmentioning
confidence: 86%
“…Consequently, a high concentration of carriers on the GaN surface can be observed [ 22 23 ]. Previous studies of graphene on GaN NWs have shown that electric charges located on the top of the GaN NWs strongly impact Raman scattering in graphene, causing an enhancement of the spectrum [ 24 25 ]. Therefore, studies of graphene on NWs with different densities and variations in height might give information about the role of supporting points on graphene properties.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Previous studies of graphene on GaN NWs have shown that electric charges located on the top of the GaN NWs strongly impact Raman scattering in graphene, causing enhancement of the spectrum. 24,25 Therefore, studies of graphene on NWs with different density and variations in height might give an information about the role of the density of supporting points under graphene on its properties. For example, analysis of graphene deposited on uniformly distributed silicon nanopillars showed the dependence of graphene strain on distances between nanopillars.…”
Section: Introductionmentioning
confidence: 99%